2024
DOI: 10.1037/aca0000441
|View full text |Cite
|
Sign up to set email alerts
|

Do art lovers lead happier and even healthier lives? Investigating the psychological and physical benefits of savoring art.

Abstract: Previous research has indicated that engaging in art activities is beneficial to both psychological and physical well-being; however, few studies have examined the link between attitudes toward art and well-being. In the present study, we have termed a positive and appreciative attitude toward art as savoring art and have investigated the relationship between savoring art and individual well-being. Study 1 (N = 501) examined the associations between savoring art and psychological well-being (PWB) as well as su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 64 publications
0
6
0
Order By: Relevance
“…Regarding well-being, we found that people who are more interested or more aesthetically responsive had a larger improvement in mood as well as less mental fatigue after the visit. As previous findings on individual characteristics and well-being outcomes were mixed (Binnie, 2010; Lee et al, 2021), future studies are needed to replicate our findings and to further investigate the link between individual characteristics and positive outcomes of art experiences. Though we did not test this link directly, these results are in line with the argument that these effects are mediated by enhanced aesthetic experience (Trupp et al, 2023).…”
Section: Discussionmentioning
confidence: 58%
“…Regarding well-being, we found that people who are more interested or more aesthetically responsive had a larger improvement in mood as well as less mental fatigue after the visit. As previous findings on individual characteristics and well-being outcomes were mixed (Binnie, 2010; Lee et al, 2021), future studies are needed to replicate our findings and to further investigate the link between individual characteristics and positive outcomes of art experiences. Though we did not test this link directly, these results are in line with the argument that these effects are mediated by enhanced aesthetic experience (Trupp et al, 2023).…”
Section: Discussionmentioning
confidence: 58%
“…To measure how much participants enjoyed and cherished art in their daily lives, we used Lee et al's (2021) savouring art questionnaire. The scale is based on six items related to art from the openness to experience scale (based on DeYoung et al, 2007) on a 7‐point Likert‐scale ranging from (1) Not at all to (7) Very much , (e.g., ‘I enjoy the beauty of art’.)…”
Section: Methodsmentioning
confidence: 99%
“…However, unlike arts engagement, the attitude towards art, known as savouring art, is the degree to which one enjoys and appreciates art in their daily lives, the attitude and need for an artistic experience (Lee et al, 2021). Lee et al (2021) based an operational definition for this concept on selected items related to art from the openness to experience scale (DeYoung et al, 2007), and found that savouring art was linked to a greater level of SWB and low biological health risk, as measured by objective biomarkers for inflammation and hypertension.…”
Section: Academic Grit Academic Achievement and Self-cultivation Char...mentioning
confidence: 99%
See 2 more Smart Citations